Ultrasonic Lamb waves detection using an unstabilized optical interferometer with uncalibrated phase shifts - Alvarez, Natalia Clara (2014)
We present an experimental and post-processing scheme that allows ultrasound surface wave detection by means of an unstabilized homodyne interferometric technique. We register interference signals for a set of uncalibrated phase shifts and, from them, we are able to retrieve the normal surface displacement of a thin aluminium plate. The results obtained with this technique are then compared to robust and more traditional phase recovery methods such as the Carré algorithm and the 11-step windowed discrete Fourier transform algorithm. For both algorithms, we found a correlation superior to 99.9%, when compared to the results of the proposed technique. This non-destructive testing scheme represents a simpler and less-expensive alternative to other existing laser ultrasonic techniques.